Hydrological potential of the southern flank of Slamet Volcano, Central Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1984)
Agricultural and industrial developments in Indonesia increase the demand for water. Because Indonesia is the most volcanic country in the world. it is important to study the water potential of volcaninc areas, such as Java which is crowned by 35 volcanoes. The study concentrates on the hidrological characteristics and potential of Slamet volcano area, Central Java. SinCe the geomorphologicÂ°, influence on hydrometeorological, geohydrological, and potamological potentials of the Slamet volcano are still unknown, this study aims at: (i) studying the relationship between the geomorphology of the Slamet volcano and the surface water and ground-water supply, (ii) calculating and evaluating the available surface water and groundwater in the fluvio volcanic foot plain and the fluvio volcanic plain of southern flank of the Slamet volcano. Method and technique used in this study are to estimate the total amount and distribution of water supply existing in the study area. Water availability is estimated from precipitation, surface water, and groundwater. Analysis of rain area distribution was conduCted using isohyetal method. Penman method, especially its modification, was used to calculate evaporation. Surface water availability is determined by precipitation-evaporation balance in addition to land surface factors. The hydrometeorological balance is obtained by using Thornthwaite-Mather. method. Geomorphology, lithology, geological structure. stratigraphy. soil. and land cover are important for the study in groundwater availability in the volcanic areas. The study in these physical elements determining geohydrological unit and groundwater distribution was conducted by using aerial photo and Landsat image interpretation accompanied by fieldchecks and supported by the interpretation of existing geological maps. From this study, it is found that the study area is able to produce 3,756,490.6 m3/day deriving from springs, unconfined aquifers, semi confined to be capable of supplying water demands for Purwokerto, i.e.: drinking water, water for public use covering domestic use, shopping centers and industries. River water here can be made use for irrigation. To sum up, hydrological potential of the study area is high. Water conservation can be conducted by forest preservation in addition to developing farm-yard culture with perennial trees and agroforestry.